2003
DOI: 10.1111/j.0014-3820.2003.tb00310.x
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Spontaneous Mutation to Variation in Environmental Response in Arabidopsis Thaliana: Responses to Nutrients

Abstract: Although the evolutionary importance of spontaneous mutation is evident, its contribution to the evolution of ecological specificity remains unclear, because the environmental sensitivity of effects of new mutations has received little empirical attention. To address this issue, we report a greenhouse in which we grew plants from 20 mutation-accumulation (MA) lines, advanced by selfing and single-seed descent from a single common founder to generation 17, as well as plants from five lines representing the foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 62 publications
0
27
1
Order By: Relevance
“…Attempts to relate mutational effects to environmental stress have produced inconsistent results (Kondrashov and Houle 1994;Fernández and Ló pez-Fanjul 1997;Shabalina et al 1997;Szafraniec et al 2001;Fry and Heinsohn 2002;Chang and Shaw 2003;Estes et al 2005;Kavanaugh and Shaw 2005). The importance of environmental effects is most closely associated with competitive fitness in Drosophila melanogaster (e.g., Shabalina et al 1997, but see Keightley et al 1998), although at least one study found no effect of competitive vs. noncompetitive conditions on the change in mean fitness (Fry and Heinsohn 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Attempts to relate mutational effects to environmental stress have produced inconsistent results (Kondrashov and Houle 1994;Fernández and Ló pez-Fanjul 1997;Shabalina et al 1997;Szafraniec et al 2001;Fry and Heinsohn 2002;Chang and Shaw 2003;Estes et al 2005;Kavanaugh and Shaw 2005). The importance of environmental effects is most closely associated with competitive fitness in Drosophila melanogaster (e.g., Shabalina et al 1997, but see Keightley et al 1998), although at least one study found no effect of competitive vs. noncompetitive conditions on the change in mean fitness (Fry and Heinsohn 2002).…”
Section: Resultsmentioning
confidence: 99%
“…In field experiments, the expectation is that more mutations will be involved in fitness, and they will have a greater effect on fitness. Stressful conditions are also known to increase the variance in mutations’ effects on fitness (Martin & Lenormand, 2006) and to result in mutations being more deleterious on average (Kondrashov & Houle, 1994 but see Chang & Shaw, 2003). For example, inbreeding depression is generally greater in more stressful versus less stressful environments (Dudash, 1990; Frankham, 2015; but see Waller, Dole, & Bersch, 2008; Agrawal & Whitlock, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, in Kishony and Leibler (2003), ⌬V is not given, so that we only report ⌬M. Finally, in two other studies of mutation effects across environments (Chang and Shaw 2003;Kavanaugh and Shaw 2005), there is no clear evidence of any fitness variance induced by mutation, in any environment, so we discarded these studies. As explained above, to estimate the effect of the environment on ⌬M and ⌬V we used log-ratio estimates of ⌬M (log[ M ]) and ⌬V (log[ V ]) in a given stressful environment relative to the estimate in the benign environment (denoted FIG.…”
Section: Survey Of Mutational Genotype-by-environmentmentioning
confidence: 98%
“…Since the work of Kondrashov and Houle (1994), several studies have documented differences in mutation effects across various environments for quantitative traits that are more or less related to fitness (reviewed in Lynch et al 1999;Fry and Heinsohn 2002;Lenormand 2002;Chang and Shaw 2003;Hermisson and Wagner 2004;Korona 2004). The im-plications of this environment dependence have been debated in an empirical and theoretical context.…”
mentioning
confidence: 99%